Exploring Youth Engagement with Sports News: A Focus Group Study (Journal of Namibian Studies : History Politics Culture, 2023)
Media is considered the mirror of society. It presents all information, news, and updates about contemporary issues. Sports news has always been an important component of daily news. Sports is essential for all age groups. However, in youth age sports have significant importance. News and Information shapes the opinions, perceptions, and also behaviours. The current study aimed to explore the youth engagement with sports news. Through Focus group discussion, the study aimed to explore the primary media sources among youth for Sports news, youths’ perception about media coverage of sports, and their pattern of consuming sports news and information. As reflected through discussion, the study found that youth actively engage in sports news through mass media as well as social media platforms and mainly follow for updates and highlights of sports events. Majority of the respondents opined that media gives good coverage to sports but they also opined that most of the coverage is focused only on Cricket. However, social media platforms provide them wide range and accessibility to follow their preferred sports interests through varied platforms dedicated to sports.